How to become a cashless economy and what are the determinants of eliminating cash - Josep Maria Raya; Claudia Vargas (Journal of Applied Economics, 2022)
This paper aims to ascertain the determinants by which individuals decide to use credit cards as a payment method rather than cash; that is, to understand changes in socioeconomic factors on the long-term use of alternatives to cash. Using the data from the waves (2002-2017) of the Spanish Survey of Household Finances (SSHF) and a panel data estimation (static and dynamic), we identify education, age, income and wealth as the main drivers of credit cards as a payment method. We disentangle the effect of age and the cohort effect. We check for nonlinearity problems and card use persistence. A secondary aim is to establish, using a controlled experiment, some of the financial consequences of being a cashless economy.
Keywords: 330; Card; cash; payment method; cashless economy